Posthumous works of Frederic II. King of Prussia / [translated from the French by Thomas Holcroft]. - Frederick II, King of Prussia, 1712-1786. (Tufts University. Tisch Library., 2016)
Volume 5 of 13.; 1 online resource (13 volumes) : portrait.; Title from half-title.; Half title. Each volume has also special t.p.; Translated by Thomas Holcroft from 'Oeuvres posthumes de Frederic II'.; Electronic reproduction. Medford, MA : Tisch Library, Tufts University, 2015. Scanned by the Boston Library Consortium/Open Content Alliance as part of the BLC OCA Digitization Project from a copy at the Tisch Library, Tufts University.; Binding: Tisch Library Special Collections print copy: Bound in contemporary tree calf, flat spine with alternating gilt embellishments in each compartment, red and green lettering pieces.; Indexed in: English Short Title Catalog,ESTCT103843